Valosin Containing Protein as a Specific Biomarker for Predicting the Development of Acute Coronary Syndrome and Its Complication - Xu, Chenchao; Yu, Bokang; Zhao, Xin; Lin, Xinyi; Tang, Xinru; Liu, Zheng; Gao, Pan; Ge, Junbo; Wang, Shouyu; Li, Liliang (Frontiers in Cardiovascular Medicine, 2022)
Background: Acute coronary syndrome (ACS) consists a range of acute myocardial ischemia related manifestations. The adverse events of ACS are usually associated with ventricular dysfunction (VD), which could finally develop to heart failure. Currently, there is no satisfactory indicator that could specifically predict the development of ACS and its prognosis. Valosin containing protein (VCP) has recently been proposed to protect against cardiac diseases. Hence, we aimed to assess whether VCP in serum can serve as a valuable biomarker for predicting ACS and its complication. Methods: Human serum samples from 291 participants were collected and classified into four groups based on their clinical diagnosis, namely healthy control (n=64), ACS (n=40), chronic coronary syndrome (CCS, n=99), and non-ischemic heart disease (non-IHD, n=88). Clinical characteristics of these participants were recorded and their serum VCP levels were detected by enzyme-linked immunosorbent assay (ELISA). Association of serum VCP with the development of ACS and its complication VD was statistically studied. Subsequently, GWAS and eQTL analyses were performed to explore the association between VCP polymorphism and monocyte count. A stability test was also performed to investigate whether VCP is a stable biomarker. Results: Serum VCP levels were significantly higher in the ACS group compared with the rest groups. Besides, the VCP levels of ACS patients with VD were significantly lower compared to those without VD. Multivariate logistic regression analysis revealed VCP was associated with both the risk of ACS (p = 0.042, OR = 1.222) and the risk of developing VD in ACS patients (p = 0.035, OR = 0.513) independently. The GWAS analysis also identified an association between an VCP polymorphism (rs684562) and monocyte count, while the influence of rs684562 on VCP mRNA expression level was further verified by eQTL analysis. Moreover, a high stability of serum VCP content was observed under different preservation circumstances. Conclusion: VCP could act as a stable biomarker in predicting the development of ACS and its complication VD.